Impact of Climate Change on Sustainable Competitive Advantage of Traditional Salt in Central Java - Badi'ah, Roudlotul; Harsanto, Budi; Kaltum, Umi; Zulham, Armen; Rahman Nidar, Sulaeman (Jurnal Mebis, 2025)
Indonesia's salt production has great potential, but is still hampered by fluctuations in quality and productivity influenced by weather factors. Dependence on the weather causes instability in salt production results, which impacts achieving salt self-sufficiency. Therefore, this study aims to analyze the influence of climate factors on the productivity and quality of traditional salt in Central Java Province, including temperature, humidity, rainfall, and wind speed. This study uses a quantitative approach, with data collected from 8 salt-producing districts/cities in Central Java with purposive sampling. Climate data was obtained from BMKG, while productivity and quality data were obtained from the Central Java DKP. The analysis technique used panel data regression with the Least Squares (OLS) approach and the Chow, Hausman, and Lagrange Multiplier tests to select the best model. The results showed that rainfall significantly negatively affected traditional salt productivity, while temperature, humidity, and wind speed did not show a significant effect. Overall, climate conditions were shown to affect salt productivity positively. Temperature and humidity have a significant positive effect on salt quality, wind speed has a significant negative effect, and rainfall has no significant effect on salt quality. Overall, climate conditions have a positive effect on salt quality. Rainfall and temperature management are essential to increase salt productivity and quality, while climate factor management will produce optimal results. The development of modern salt production technology that reduces dependence on extreme weather and better management of natural resources and technology can support the achievement of more stable and sustainable salt self-sufficiency.